Analisis Kemampuan Calon Guru Penggerak (CGP) Sebagai Pemimpin Pembelajaran Yang Menerapkan Prinsip Merdeka Belajar - Saulim DT Hutahaen; Theo Jhoni Hartanto; Suhartono Suhartono; Dermawati S. (Jurnal Ilmiah Kanderang Tingang, 2022)
The essence of independent learning is the freedom of teachers and students in the learning process. This freedom has not been experienced by teachers and students so far because teachers are more involved in the administration of education and learning. Teachers also do not understand the concept and its role in the policy of independent learning. The purpose of this study is to explain the concept and meaning of independent learning, the role of teachers in independent learning. The method used is the library method. Content analysis was used to analyze research data. The results of this study are (1) independent learning includes 4 policies, namely national standard school exams carried out by the school, minimum skill assessments and character surveys, simplification of lesson plans, zoning system for new student admissions; (2) the meaning of independent learning includes freedom of thought, freedom to innovate, independent and creative learning, freedom for happiness; (3) the role of teachers varies widely, including facilitators of independent learning, innovative and creative teachers, teachers with the characteristics of teachers, and driving teachers. Based on this explanation, this study concludes that understanding the meaning of independent learning and the role of teachers in independent learning helps teachers and students be more independent in thinking, more innovative and creative, and happy in learning activities. The six aspects of the Pancasila Student Profile must be owned by students and teachers in order to achieve the goal of Independent Learning. This is also the reason for the existence of the Motivating Teacher program because its establishment aims to fulfill these six aspects. The six aspects of the Pancasila Student Profile formulated by the Ministry of Education and Culture are: 1) Faithful, devoted to God Almighty and with Noble Morals, 2) Creative, 3) Mutual Cooperation, 4) Global Diversity, 5) Critical Reasoning, 6) Independent. A good teacher is a teacher with good performance but only in the classroom. They are able to improve student achievement, teach creatively and innovatively, and develop their own competence. Meanwhile, the role of the Motivating Teacher is not only limited to success in managing the class he or she is teaching. In addition to being a good teacher, a Motivating Teacher must also have the will to lead, innovate, and make changes. On this basis, Kejarcita is here to support teachers to become professional driving teachers.